360=(x+40)+(4x+70)+(2x+110)

Simple and best practice solution for 360=(x+40)+(4x+70)+(2x+110) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 360=(x+40)+(4x+70)+(2x+110) equation:


Simplifying
360 = (x + 40) + (4x + 70) + (2x + 110)

Reorder the terms:
360 = (40 + x) + (4x + 70) + (2x + 110)

Remove parenthesis around (40 + x)
360 = 40 + x + (4x + 70) + (2x + 110)

Reorder the terms:
360 = 40 + x + (70 + 4x) + (2x + 110)

Remove parenthesis around (70 + 4x)
360 = 40 + x + 70 + 4x + (2x + 110)

Reorder the terms:
360 = 40 + x + 70 + 4x + (110 + 2x)

Remove parenthesis around (110 + 2x)
360 = 40 + x + 70 + 4x + 110 + 2x

Reorder the terms:
360 = 40 + 70 + 110 + x + 4x + 2x

Combine like terms: 40 + 70 = 110
360 = 110 + 110 + x + 4x + 2x

Combine like terms: 110 + 110 = 220
360 = 220 + x + 4x + 2x

Combine like terms: x + 4x = 5x
360 = 220 + 5x + 2x

Combine like terms: 5x + 2x = 7x
360 = 220 + 7x

Solving
360 = 220 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
360 + -7x = 220 + 7x + -7x

Combine like terms: 7x + -7x = 0
360 + -7x = 220 + 0
360 + -7x = 220

Add '-360' to each side of the equation.
360 + -360 + -7x = 220 + -360

Combine like terms: 360 + -360 = 0
0 + -7x = 220 + -360
-7x = 220 + -360

Combine like terms: 220 + -360 = -140
-7x = -140

Divide each side by '-7'.
x = 20

Simplifying
x = 20

See similar equations:

| x+47=54 | | 4x^2-2-8w=-6x | | -14x+1=21 | | 360=(x+50)+(2x+80)+(4x+20) | | x^4-5x^3-2x^2-3x-9= | | 5y-(3y+8)=3-(7y-9) | | 5(x-1)=3(2-x)-5 | | x+52=61 | | 11v-2v=54 | | x+78=86 | | 90x^2-63xy+18x=0 | | 7=m/125 | | -3.5b-1.75c= | | 4X+20=25-x | | x-2(-2x+20)=20 | | c/2=-14 | | X^2+27x-18=0 | | d=7.25t | | 1.1x=94000 | | -4(2t+5)=-60 | | 24x+7x=19 | | =11x+5y-30z | | 2^3x=1/8 | | -10(s+4)=-78 | | 2.5=0.6*[19.6(1-.61*x)]^(1/2)*2*x | | 324x^4-4y^4= | | 2/386/7 | | x/3-4#8 | | (x-2/3)^2-(y-1/4)^2=49 | | 48x^3-78.4x^2+16.8=0 | | -6-2y+4= | | (2b-c)-(1.5b+.75c)= |

Equations solver categories